Modeling of the cancer thermal therapies from the perspective of parametric sensitivity and improved treatment planning - Muhammad Jamil (2014)
The scope of this thesis covers the improved efficacy of the thermal therapies of capacitive hyperthermia and radiofrequency ablation (RFA). Additionally, it deals with the simulation of bioheat transfer with a novel numerical method that makes use of its meshless characteristic to provide the optimum simulation results. For capacitive hyperthermia, the effect of electrothermal parameters as well as physical parameters was quantified and regression based prediction model was formulated. Additionally, a novel meshless method known as Radial Basis Collocation Method (RBCM) has been applied to simulate the heterogeneous conduction and bioheat transfer problem. Research was carried out to analyze the efficacy of radiofrequency ablation (RFA) for varying electrothermal parameters under fixed temperature control and their combined effect was analyzed quantitatively in different tissues. Additionally, the effect of electrothermal parameters for concentric tumour model was analyzed under automatic temperature control. Simplified models models were utilized for prediction of therapeutic outcome.